Improving Comprehensive Medication Management (CMM) Completed Visit Rates in Newly Referred and No-Show Patient Cohorts - Michelle Tran; Yookyung Christy Choi; Amanda Brummel; Heidi Burres; Jean Moon; Allyson Schlichte; Kelly Schweim (University of Minnesota Libraries Publishing, 2019)
Background: Missed appointments are a common problem in health care. No-show rates and incomplete appointments for referred patients affect patient outcomes and clinician's productivity, including comprehensive medication management (CMM) visits that pharmacists provide. This study aims to compare CMM completion rates between various intervention types in communicating with the patient. Methods: This was a prospective, multi-clinic study to examine newly implemented intervention effects on CMM completion rates. The primary outcomes were CMM completion rates among newly referred patients and CMM completion rates in any no-show patients, including both newly referred and returning patients. In the newly referred patient cohort, three intervention types (blocking time on the pharmacist's schedule to speak to the patient, sending an electronic medical record or EMR-linked message, and sending a letter) were compared to a control group with no interventions. In the no-show cohort, a pharmacist call intervention was compared to a control group consisting of sending a letter. Results: Completed CMM appointment rate was six times likely with a pharmacist's in-person reminder (odds ratio [OR] 6.0; 95% confidence interval [CI] 1.58-22.77) and with an EMR-linked message (OR 6.0; 95% CI 1.76 to 20.52) when compared to sending a letter. In no-show patients, completed CMM appointment rate was 2.36 times likely with a pharmacist's call intervention versus sending a letter. Conclusion: Pharmacist's direct reminder to the patient when in clinic and EMR-linked message improved CMM completion rate when compared to mailing a reminder letter. Pharmacist's call to no-show patients for their CMM appointment was effective for the patients to reschedule and complete their CMM appointment compared to mailing a reminder letter.   Article Type: Original Research